Efects of bromelain on cellular characteristics and expression of selected genes in canine in vitro chondrocyte culture - Siengdee P. (2014)
The purpose of this study was to determine the effect of bromelain treatment on canine articular chondrocytes in vitro. This research evaluated cell viability, levels of apoptotis and mitotis, proteoglycan concentrations and the expression of certain genes. Chondrocytes were exposed to 50 μg/ml bromelain for 4, 16 and 32 h. The rate of apoptotis in the treatment groups was significantly lower than in the control groups that were incubated with media only (P < 0.05); and the mitotic rate in treatment groups was significantly higher than in the control groups (P < 0.05), at all durations of exposure. The effect of bromelain on gene expression was measured by the real-time PCR technique. It was found that bromelain significantly decreased (P < 0.05) TIMP-1 and MMP-3 expression. These experimental bromelain treatments have shown positive results, and have increased the basic knowledge in regard to the healing and modulation of osteoarthritis, prior to the general use of bromelain in clinical practice.